(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Platelets are one of the most important cells in human blood, and help control bleeding. Mean platelet volume (MPV) play a vital role to indicate the activation of platelets. any significant changes of mean platelet volume will effect on platelet activity. Vibration-stimulats changes in the platelets activity as a type of stress upon MPV. This study aimed to investigate the impact of ultrasound waves on MPV of healthy and hypertension subjects in vitro model study. Venous blood samples obtained from healthy subjects (n=43 ) and hypertensive patients (n=61 ) have been exposed to ultrasound waves for two periods (5-10) minutes. The MPV was measured using the Coulter electronic count (Complete blood Count). The results have been showen that ultrasound waves caused a significant changes MPV in healthy subjects and hypertensive patients. The changes in the MPV are dependently related to the exposure time. In healthy subjects, the MPVs have been significantly increased by 12.6% for 10-min exposure while in hypertensive are significantly decreased by 9.1% for 10-min. It concludes that ultrasound induced an increase of the MPV, and this effect is tended to be less in patients with hypertension indicated that the responses of platelets are reduced in chronic diseases. It is clearly indication that the cellular response of MPVs in hypertension patients were very weak may because of hypertension. Whereas, MPVs response of healthy subject remained normal and effective.